Exposure of the hands to ionizing radiation in the resuscitation room of an accident & emergency department. Issue 2 (June 1992) - Evans, R J; Cusack, S; Parke, T
Abstract : Exposure of the hands to ionizing radiation in the resuscitation room of an A&E department was measured in eight health care personnel over 3 consecutive months. The radiation levels did not exceed those limits currently recommended by the International Commission on Radiological Protection 1990. The level recorded in one individual did exceed the level set at the Lothian Health Boards investigation limit. In only five of 85 occasions were lead gloves worn by the doctor during cross table lateral cervical radiographs. Recommendations are made for reducing the radiation exposure to the hands.